Estimation of adaptivity of economy of Kazakhstan to membership in ЕАEU in the context of activation of processes of increase of competitiveness (Journal of Economic Research & Business Administration, 2015)
This article considered the problem of the influence of economic integration in the competitiveness of the Kazakhstani economy, particularly the agro-industrial sector. These influences are both positive and negative. An analysis of the main economic features of the agro-cultural industries of Kazakhstan, Russia, and Belorussia revealed changes in agro-cultural competitiveness. Authors consider that the estimation of competitiveness of agroindustrial complex must come true not absolute, and by relative indexes: the productivity of agricultural culture, productivity of cattle and bird, index of clean export, profitability of production, degree of wear of the fixed assets, volume of products per capita. On the basis of the conducted analysis authors came to the conclusion, that each a country-partner on ЕАEU has the comparative advantages that must be taken into account at forming of single market of food within the framework of the Eurasian economic union.
Keywords: economic integration; agroindustrial complex; competitiveness